A De Novo Missense MYLK Variant Leading to Nonsyndromic Thoracic Aortic Aneurysm and Dissection Identified by Segregation Analysis - Daigo Nishijo; Hiroki Yagi; Nana Akiyama; Norifumi Takeda; Masahiko Ando; Haruo Yamauchi; Norihiko Takeda; Issei Komuro (Case Reports in Genetics)
Nonsyndromic hereditary thoracic aortic aneurysm and dissection (TAAD) is an autosomal dominant disease; however, it is frequently difficult to identify the causative genes. We report in this study a 33-year-old Japanese male with TAAD (Stanford type A) that is complicated with severe aortic regurgitation. There was no family history of aortic diseases in the patient nor any specific clinical features suggestive of connective tissue diseases, such as Marfan syndrome. Genetic testing identified candidate causative variants in two different genes: MYLK (c.4819G > A, p.[Gly1607Ser]) and FBN1 (c.365G > A, p.[Arg122His]). Familial cosegregation analysis revealed that the novel de novo MYLK variant was present only in the proband, and the FBN1 variant was also found in his nonaffected mother, and thus the MYLK variant was classified as likely pathogenic. MYLK is a causative gene for nonsyndromic TAAD that requires careful management; however, the number of reports is limited. Accumulating data on the pathogenicity of rare variants by performing a comprehensive pedigree analysis would help establish better treatment strategies for life-threatening hereditary TAAD cases.